Islamic Religious Identity in Contemporary Kyrgyzstan - Jibrail Bin Yusuf; Aikol Boletbekova; Jabal Muhammad Buaben; Hassan Shakeel Shah; Muhammad Ayaz (International Journal of Islamic Khazanah, 2023)
This paper assesses the state of Islam in Post-Soviet Kyrgyzstan. It examines the challenges Islam faces due to the diversity of ideologies bequeathed by the Soviet Union. Although Islam emerged as a dominant religious belief in post-Soviet Kyrgyzstan, due to the internal elements of secularism, Tengrism, and other indigenous ideologies, and the interpretation of Islamic lore coupled with the Soviet ideology of atheism, Islam remains syncretic with some loose extremism fuelled by home-grown socio-political factors and imported fundamentalism. It, therefore, concludes that the challenge to Islam and Islamic religious identity in contemporary Kyrgyzstan is a sort of ‘Muslimo-phobia’ rather than ‘Islamo-phobia’ because the challenge to Islam is clearly unleashed by the Muslims themselves and not the minority non-Muslim population.